Analysing the concept of freedom of expression in media: Article 10 of the European Convention of Human Rights - Muciņa, Laura Loreta (Riga Graduate School of Law, 2023)
Free and independent media is the cornerstone of a functioning democracy and plays an important role on informing and exposing different political and social aspects and therefore acting as ‘public watchdogs’. Article 10 of The European Convention on Human Rights is considered one of the fundamental freedoms. The Court in this matter has set a comprehensive case-law to assess the scope of freedom of expression and its interferences. The problem arises when to determine the balance of rights and duties of the media and rights of others, including the protections and safety of the country and the society. There are numerous justifications for interferences therefore when and how media can operate under the Convention and when the governing bodies can interfere with media’s work. A responsible media and journalism is imperative at all times.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::International law; Human rights law; freedom of expression; European Convention on Human Rights